Pragmatic Approach in the Design of Depth Classification Schedule:A Case Study - Neelameghan, A.; Gopinath, M. A. (Journal of Information and Knowledge, 2000)
Based on the incidence of (QJ) in the subjects going with the (BC) Production Engineering of Internal Combustion Engine, confirms the remarkable usefulness of the Wall-Picture Principle in deriving a helpful sequence among. the (QI). Explains where and how the Group  Strategy can be adopted in the application of the same Principle. Points out the conditions and restrictions laid down in the idea plane and in the notational plane which call for a careful allocation of the sectors to the (QI). Study of the incidence of the combination of (QI) in 507 (eN) shows that the superimposition of too many (QI) is comparatively rare, that the mode of the curve for the incidence of the combination of (QI) lies between combination of 2 (QI) and that of 3 (QI), and that there are no combinations of more than 11 (QI). After classifying over 600 micro documents in the subject with the provisional schedule, works out a revised allocation of sectors such that over 1,100 digits are saved in the (CN) for 507 documents.